2016
DOI: 10.1039/c5nr08155f
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced photoresponse in dye-sensitized solar cells via localized surface plasmon resonance through highly stable nickel nanoparticles

Abstract: We demonstrated the localized surface plasmon resonance (LSPR) effect of Ni nanoparticles (NiNPs) on the performance of dye-sensitized solar cells (DSSCs). Our study revealed that NiNPs in a conventional I(-)/I3(-) electrolyte (NiNPs@I(-)/I3(-)) increased the net optical absorption of a N719 dye over a broad wavelength range by LSPR, and concurrently improved the power conversion efficiency (PCE) in DSSCs. At an optimized concentration of the NiNPs@I(-)/I3(-) electrolyte (1 mg mL(-1)), N719-sensitized DSSCs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 57 publications
(67 reference statements)
0
16
0
Order By: Relevance
“…For the replacement of Pt-CE, numerous studies have demonstrated, using, for example, carbonaceous materials (e.g., graphene, carbon nanotubes, active carbon, graphite, carbon black) [ 12 ], conducting polymers (CPs) (e.g., polyaniline, polypyrrole, and poly(3,4-ethylene dioxythiophene) (PEDOT: PSS)) [ 13 ], transition metal compounds (e.g., carbides, nitrides, oxides) [ 14 ], and various hybrids or composites materials [ 15 ], which are about 10 to 10,000 times cheaper than that of Pt-CE [ 10 ]. Among them, nanostructures of metallic Ni and its compounds (e.g., oxides, sulfides, ternary sulfides, phosphides) are potentially suitable CE materials because of their decent corrosion resistance to the I − /I 3 − redox mediator and low cost [ 11 , 16 , 17 , 18 , 19 , 20 ]. However, their electrocatalytic activity for the redox reaction of I − /I 3 − and electrical conductivity is inadequate for developing high-performance DSSCs [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the replacement of Pt-CE, numerous studies have demonstrated, using, for example, carbonaceous materials (e.g., graphene, carbon nanotubes, active carbon, graphite, carbon black) [ 12 ], conducting polymers (CPs) (e.g., polyaniline, polypyrrole, and poly(3,4-ethylene dioxythiophene) (PEDOT: PSS)) [ 13 ], transition metal compounds (e.g., carbides, nitrides, oxides) [ 14 ], and various hybrids or composites materials [ 15 ], which are about 10 to 10,000 times cheaper than that of Pt-CE [ 10 ]. Among them, nanostructures of metallic Ni and its compounds (e.g., oxides, sulfides, ternary sulfides, phosphides) are potentially suitable CE materials because of their decent corrosion resistance to the I − /I 3 − redox mediator and low cost [ 11 , 16 , 17 , 18 , 19 , 20 ]. However, their electrocatalytic activity for the redox reaction of I − /I 3 − and electrical conductivity is inadequate for developing high-performance DSSCs [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…(1) They show strong localized surface plasmon resonance (LSPR) phenomena, which can enhance IR light absorption to improve the photo-thermal conversion. [24][25][26] and (2) more defect sites, which can enhance the adsorption of substrate molecules. At the same time, defect sites also decrease the CO2 reduction barrier, thus, enhancing the performance of photocatalytic conversion of CO2 [27] due to photogenerated electrons that determine the reduction reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nature of transition metals, nanosized nickel has found applications in the fields of magnetic devices, 1,2 catalysts, 3,4 batteries, 5 fuel cells, 6,7 and solar cells, 8 among others. Hence, the synthesis of Ni nanoparticles has attracted considerable attention.…”
Section: ■ Introductionmentioning
confidence: 99%